Knowledge, democracy and action Community-university research partnerships in global perspectives - Fontan, Jean-Marc; Lall, Nirmala; Tandon, Rajesh; Jackson, Edward T., 1951-; Hall, Budd L.; Project Muse; Project Muse. (Project Muse, 2017)
Knowledge, democracy and action: Community-university research partnerships in global perspectives is based on a three-year international comparative study undertaken by the Global Alliance on Community Based Research and supported by the UNESCO Chair in Community Based Research and Social Responsibility in Higher Education. It provides evidence from twenty case studies around the world on the power and potential of community and higher education based scholars and activists working together in the co-creation of transformative knowledge. The book draws on the experience and insights of thirty-seven scholars and practitioners from the Global South and North. Opening with a theoretical overview of knowledge, democracy and action, the book is followed by analytical chapters providing lessons learned and capacity building in the north and the south, on the theory and practice of community university research partnerships, models of evaluation, approaches to measuring the impact and an agenda for future research and policy recommendations.
part I. Introduction -- 1. Knowledge, democracy and action : an introduction / Budd L. Hall -- 2. Building blocks of partnerships : lessons from case studies from the South and North / Rajesh Tandon and Edward T. Jackson -- 3. An architecture understood : effective support structures for community-university partnerships / Edward T. Jackson, Letlotlo Gariba and Evren Tok -- 4. Building community-based research capacity with communities : the PRIA experience / Mandakini Pant -- 5. Curricular and pedagogical impacts of community-based research : experiences from higher education institutions / Felix M. Bivens -- 6. Embedding community-university partnerships : science shops and policy development / Eileen Martin, Emma McKenna, Henk Mulder and Norbert Steinhaus -- 7. Evaluating the research partnership process / Jean-Marc Fontan and Denis Bussi{grave}eres -- 8. Measuring the impact of community-university research partnerships : a global perspective / Nirmala Lall -- part II. Case studies -- 9. Student community engagement for employability and entrepreneurship in Senegal / Lamine Kane, Aliou Guiss{acute}e and Latyr Diouf -- 10. PRIA educates the community / Mandakini Pant -- 11. Mobilizing and strengthening knowledge for sustainable development in India / Mandakini Pant -- 12. Enhancing local policymakers' capacity in environmental governance in the Philippines / Joy Molina Mirasol, Felix S. Mirasol, Jr., Estela C. Itaas and Benjamin Maputi -- 13. Interdisciplinary research programme in Chiapas / Felix M. Bivens -- 14. Cooperation in Jesus de Machaca in Bolivia / Jos{acute}e Blanes Jim{acute}enez and Edgar Antonio Pabon -- 15. Co-operation in small forest producers in Bolivia / Jorge T{acute}ellez Carrasco and Jos{acute}e Blanes Jim{acute}enez -- 16. Evaluation of quality of drinking water in Romania (science shops) / Norbert Steinhaus -- 17. Pollution levels in local lakes in Denmark / Norbert Steinhaus -- 18. Community-University Partnership Programme (CUPP), University of Brighton / Felix M. Bivens -- 19. MA in participation, power and social change at University of Sussex / Felix M. Bivens -- 20. Cheers!? a project on alcohol and older people in Brighton / Julie Millican and Angie Hart -- 21. The Bouncing Back Project : health and social welfare of disadvantaged families in Brighton and Hastings / Kim Aumann and Angie Hart -- 22. The outreach programme at Sewanee, University of the South, USA / Felix M. Bivens -- 23. Social financing, social economy : Chantier de l'Economie Sociale Trust, Montreal / Jean-Marc Fontan and Denis Bussieres -- 24. Aboriginal transitions research project in British Columbia, Canada / Sarah Cormode -- 25. Participatory sustainable waster management in Brazil / Crystal Tremblay and Sarah Amyot -- 26. Innovative teaching and learning programmes from the CDRC / Felix M. Bivens -- -- Pt. III : Concluding remarks -- 27. Agenda for the future / Budd L. Hall. Edward T. Jackson, Rajesh Tandon, Jean-Marc Fontan, Nirmala Lall.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages 206-217) and index.
Description based on print version record.
Keywords: Education, Higher -- Social aspects -- Case studies; Community development -- Case studies; Research -- Citizen participation -- Case studies; Community and college -- Case studies; Education, Higher -- Social aspects; Community development; Research -- Citizen participation; Community and college; Electronic books; Electronic books